PENGARUH K3 PADA MOTIVASI DAN KINERJA KARYAWAN (Studi Pada Karyawan PT. YTL – Paiton- Jawa Timur) - Ikaningtyas, Maharani; Al Musadieq, Mochammad; Prasetya, Arik (Profit: Jurnal Adminsitrasi Bisnis, 2019)
The growth of the company can be seen from how big the employee could be contribute to the company. This issue could been know form the growth of Human Resources (HR) and also the results of work that can complete the company targets. Occupatiional Safety and Health Program consists of guarantees of work accidents and occupational health that are expected to be good for employee performanc. This research is an explanatory type of research. Data collection can be used using a questionnaire. The research uses probability sampling technique that is proportional random sampling. The number of samples obtained was 78 respondents from the calculation of Slovin. analysis data used the path analysis method. The resultts of this study prove that work safety is significant for work motivation’s. Work health is positive to work motivatiion. As well as positive and significant work motivation on employee performance.